Emprego de biofiltro de pedra para remoção de microalgas e sólidos suspensos de efluentes de lagoas de estabilização - Queiroz, Moisés Andrade de Farias (2014)
This research evaluated the microalgae removal produced in a stabilization pond system using biofilters as post-treatment, besides characterizing the effluents of stabilization ponds and filters in relation to concentrations of algal biomass (chlorophyll a and suspended solids), organic matter (BOD and COD), total phosphorus, orthophosphate, pH and dissolved oxygen, and tried to correlate physicochemical parameters with chlorophyll "a". It was held at the Ponta Negra ETE which is constituted by three stabilization ponds, with a primary facultative pond and two of maturation. For the algae removal were used two submerged bio-filters: the filter FPF (Facultative Pond Filter), fed with facultative pond effluent; and the filter MPF (Maturation Pond Filter), fed with second maturation pond effluent. The filling material of both filters was predominantly gravel no. 2, although it contains portions of gravel no. 1 and no. 3. The filters operating conditions were bad, they were nearly 10 years without maintenance, without cleaning or removal of sludge since the time of its construction, and part of the filling material may be obstruct. Despite poor operating conditions were obtained satisfactory results, in level of posttreatment. Removal efficiencies in relation to BOD and COD were 7 and 25% in FPF and 9 and 19% and in MPF, respectively. In relation to TSS efficiencies in MPF and FPF were 37 and 20%, respectively. As for the chlorophyll "a" removal, the FPF efficiency was 44% and the MPF was 40%. There was 50% of consumption of dissolved oxygen, on average, within the filters. Two profiles were performed in the filters, and it was possible to conclude that variations throughout the day were not statistically significant, and that, regardless of the time of collection, they would have the same representation comparing to the time of data collection (7 am) and the daily average, although individual variations throughout the day have been shown to be significant. Another important observation is that the correlations between Chlorophyll a and TSS were bigger and more significant in the effluent of the filters than in the effluent of the ponds